Surrogates for the Assessment of Robotic Manipulators Reliability - Lara-Molina, Fabian Andres; Koroishi, Edson Hideki; Machida, Jaqueline Sayuri (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2021)
This paper presents a comparative study of the methods based on the probabilistic approach and fuzzy theory to evaluate the kinematic reliability of manipulators. The kinematic reliability is a measure that evaluates if the positioning errors overpass acceptable limits by considering the uncertainties of the manipulator. In this direction, two main approaches are considered based on the probabilistic theory and the fuzzy theory to evaluate the kinematic reliability. The Monte Carlo simulation, first-order reliability method (FORM), and the second-order reliability method (SORM) based on the probabilistic approach were used by following the probabilistic theory. Moreover, the possibility of failure was deduced based on fuzzy methods. Finally, the methods were validated in a 3R serial manipulator by using numerical simulations.